2022
DOI: 10.3390/mi13111930
|View full text |Cite
|
Sign up to set email alerts
|

A DSSC Electrolyte Preparation Method Considering Light Path and Light Absorption

Abstract: The electrolyte is one of the key components of dye-sensitized solar cells’ (DSSC) structure. In this paper, the electrolyte formulation of a new DSSC with external photoanode structure was studied. Based on the idea that the electrolyte should match the light absorption and light path, iodine series electrolytes with different concentrations were configured and used in the experiment. The results showed that the external photoanode structure solar cells assembled with titanium electrode had the best photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[ 53 ] OXA, a first‐line chemotherapy drug approved for CRC or advanced CRC worldwide, can provoke ferroptosis in CRC by suppressing the Nrf2 signaling pathway. [ 10,54 ] But OXA resistance emergence is also a challenging factor responsible for the failure of CRC treatment. [ 27 ] In our study, we unexpectedly observed that FOXA2 expression was positively correlated with GPX4, Nrf2, NQO1, and SLC7A11 in CRC patients from the TCGA database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 53 ] OXA, a first‐line chemotherapy drug approved for CRC or advanced CRC worldwide, can provoke ferroptosis in CRC by suppressing the Nrf2 signaling pathway. [ 10,54 ] But OXA resistance emergence is also a challenging factor responsible for the failure of CRC treatment. [ 27 ] In our study, we unexpectedly observed that FOXA2 expression was positively correlated with GPX4, Nrf2, NQO1, and SLC7A11 in CRC patients from the TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, targeting GPX4 may be an efficient approach to induce ferroptosis. [ 36,54,58 ] More recently, FOXA2 was reported to mediate Nrf2 target genes in fumarate hydratase‐deficient cells, and its knockdown decreased the expression of Nrf2 target genes, thus altering anti‐oxidant associated metabolites. [ 59 ] Similar influence of sh‐FOXA2 on Nrf2 signaling was observed in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…Several other factors are also thought to influence the low value of the resulting voltage, including the thickness of the TiO 2 decomposition layer and the use and concentration of the electrolyte used [37,38].Overall, the DSSC produced is capable of being assembled into panels. However, several things can be done to get more optimal results, including characterization tests for TiO 2 nanoparticles before being decomposed into ITO glass [39], selecting a more appropriate electrolyte [40], and then testing current and power efficiency to show the best performance DSSC made. As a result, when DSSC is implemented in the form of panels and installed in a series of tools, such as solar car kits, it is not inferior to the quality of solar panels that are often sold in society.…”
Section: Discussionmentioning
confidence: 99%
“…The electrolyte is a significant component in the DSSC as an internal charge carrier between the metal oxide and the electrode (Yang et al, 2022). In the application of the DSSC circuit, there are 3 types of electrolytes, namely liquid, solid, and quasi-solid states.…”
Section: Solid Electrolytementioning
confidence: 99%